Numerical Determination of the Accuracy of Gravity Center Coordinates and Stability of a Model Concept of Harvester with the Rigid Frame - Mergl, Václav; Kašpárek, Jaroslav (MDPI, 2022)
The paper deals with the verification of the stability of a new design concept of a hybrid harvester intended for thinning and with the determination of deviation between two methods of measuring the machine's center of gravity, i.e., between the methods of determining the center of gravity using the SolidWorks software made by Dassault Systems and using portable vehicle scales with the function of gravity center calculation. The machine was measured in five different positions from going up or down the slope or driving along the contour line. The new prototype of a harvester with a non-conventional rigid frame and both axles steered was found to be unstable at the maximum reach of hydraulic boom if it is situated at a right angle (+/- 90 degrees) to the machine longitudinal axis. A comparison of the two methods of determining the center of gravity resulted in a total deviation of 8.41%, with the deviation for x being on average 14.36% and for y only 3.08%.

The paper deals with the verification of the stability of a new design concept of a hybrid harvester intended for thinning and with the determination of deviation between two methods of measuring the machine's center of gravity, i.e., between the methods of determining the center of gravity using the SolidWorks software made by Dassault Systems and using portable vehicle scales with the function of gravity center calculation. The machine was measured in five different positions from going up or down the slope or driving along the contour line. The new prototype of a harvester with a non-conventional rigid frame and both axles steered was found to be unstable at the maximum reach of hydraulic boom if it is situated at a right angle (+/- 90 degrees) to the machine longitudinal axis. A comparison of the two methods of determining the center of gravity resulted in a total deviation of 8.41%, with the deviation for x being on average 14.36% and for y only 3.08%.
Numerical Determination of the Accuracy of Gravity Center Coordinates and Stability of a Model Concept of Harvester with the Rigid Frame
Keywords: harvester; CTL (cut to length) technology; rigid frame; stability; center of gravity; deviation; hydraulic loader boom; machine position; harvester; CTL (cut to length) technology; rigid frame; stability; center of gravity; deviation; hydraulic loader boom; machine position